Does oil price volatility matter for the US transportation industry? - Dutta, Anupam; Bouri, Elie; Rothovius, Timo; Azoury, Nehme; Salah Uddin, Gazi (Elsevier, 2023)
Although the US transport sector is one of the major users of fossil fuel (e.g., crude oil), the impact of energy price volatility on transport stock sector indexes remains under-researched. The present study addresses this research void by investigating the impact of energy implied volatility on transportation stock returns in the US. Using the crude oil volatility index (OVX), as a proxy of energy price volatility, and three Dow Jones indexes tracking the performance of the airlines, marine and trucking stock subsectors, we employ a GARCH-jump model. The main results show that the oil market sends volatility to the US transport subsector stock indexes, suggesting that oil implied volatility plays a role in pricing US transport stocks. The impact of OVX shocks is asymmetric, indicating that increases and decreases in oil implied volatility have a heterogeneous impact on the transport subsector stock markets. Jumps are significant in the three transport subsector stock indexes, and are time-dependent. Notably, the three transportation subsector stock indexes are more sensitive to OVX shocks than the S&P 500 index. These results have important implications for investors, policymakers, academics, and managers of the US transportation industry.
Keywords: US transport sector returns; Oil implied volatility (OVX); COVID-19 outbreak; GARCH-Jump; Asymmetric effect; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|